Supporting tasks used by teachers to develop the skills of reading and writing in the teaching - learning of the English language, in the eighth year of basic education in Aurelio Prieto Muelas, Carmen Mora de Encalada and Dr. Jose Ochoa Leon high schools in Pasaje city, during the period 2013 -2014. - Zari Chuchuca, María Elizabeth (2014)
As time has passed , the English language has had a high growth worldwide and particularly in Ecuador , because it has become a valuable tool for communication in our daily lives .